The Influence of Attitude, Subjective Norms, and Behavioral Control on the Purchase Intentions of Maybelline Cosmetics in Bandar Lampung - Agustini, Putri Ayu; Roslina, Roslina (LPPPIPublishing, 2024)
This study examines the influence of attitude, subjective norm, and perceived behavioral control on the purchase intention of Maybelline cosmetic products in Bandar Lampung. Using a descriptive quantitative approach, data was collected through surveys and interviews with Maybelline users in Bandar Lampung. The findings indicate that all three factors—attitude, subjective norm, and perceived behavioral control—positively and significantly affect consumers' purchase intentions. Consumers’ attitudes towards Maybelline are shaped by product quality, innovation, and its ability to meet beauty needs. Subjective norms, influenced by social factors such as recommendations from friends and influencers, also drive purchase decisions. Furthermore, behavioral control, based on consumers’ perception of their ability to afford and use Maybelline products, plays a critical role in their purchasing decisions. The study suggests that Maybelline can enhance its market position by focusing on sustainability, promoting transparent reviews, and offering affordable product bundles. Collaborations with influencers and popular figures can also strengthen emotional connections with consumers and further encourage purchase intentions. The research provides valuable insights into how attitude, social influence, and perceived control impact consumer behavior, offering practical implications for marketers in the cosmetics industry.